Link N as a therapeutic agent for discogenic pain. Issue 1 (15th March 2018) - Noorwali, Hussain; Grant, Michael P.; Epure, Laura M.; Madiraju, Padma; Sampen, Hee‐Jeong; Antoniou, John; Mwale, Fackson
Abstract : We provide evidence that the bioactive peptide Link N can suppress the expression of NGF, BDNF and their receptors TrkA and TrkB respectively, in human intervertebral disc cells in an inflammatory milieu. Therefore, administration of Link N has the potential to not only repair discs in early stages of disease but also suppress pain. Abstract : Neurotrophins (NTs) are the major contributors of sensory axonal sprouting, neural survival, regulation of nociceptive sensory neurons, inflammatory hyperalgesia, and neuropathic pain. Intervertebral disc (IVD) cells constitutively express NTs. Their expression is upregulated by proinflammatory cytokines present in the IVD during degeneration, which can promote peripheral nerve ingrowth and hyperinnervation, leading to discogenic pain. Currently, there are no targeted therapies that decrease hyperinnervation in degenerative disc disease. Link N is a naturally occurring peptide with a high regenerative potential in the IVD. Therefore, the suitability of Link N as a therapeutic peptide for suppressing NTs, which are known modulators and mediators of pain, was investigated. The aim of the present study is to determine the effect of Link N on NTs expression, nerve growth factor (NGF), brain‐derived neurotrophic factor (BDNF), and their cognate receptors TrkA and TrkB as they are directly correlated with symptomatic back pain. Furthermore, the neurotransmitter (substance P) was also evaluated in human annulus fibrosus (AF) cells stimulated with cytokines. Human AF cells isolated from normal IVDs were stimulated with interleukin‐1β (IL‐1β) and tumor necrosis factor‐α (TNF‐α) in the presence or absence of Link N. NGF release in the media was evaluated by Western blotting. Total RNA was isolated and gene expression was measured using real‐time PCR. Gene expression of NGF, BDNF, TrkA, and TrkB significantly decreased in human disc cells stimulated with either IL‐1β or TNF‐α supplemented with Link N when compared to the cells stimulated only with IL‐1β or TNF‐α. NGF protein expression was also suppressed in AF cells coincubated with Link N and IL‐1β when compared to the cells stimulated only with IL‐1β. Link N can suppress the stimulation of NGF, BDNF, and their receptors TrkA and TrkB in AF cells in an inflammatory milieu. Thus, coupled with previous observations, this suggests that administration of Link N has the potential to not only repair the discs in early stages of the disease but also suppress pain.